Berdreymi = Beautiful beings [videorecording (DVD)] - Guðmundur Arnar Guðmundsson; Birgir Dagur Bjarkason; Áskell Einar Pálmason; Viktor Benóný Benediktsson; Snorri Rafn Frímannsson; Briem, Anita; Ísgerður Gunnarsdóttir; Ólafur Darri Ólafsson (Altered Innocence, 2023)
Iceland's official submission to the Academy Awardsʼ for Best International Feature Film! Addi, a boy raised by a clairvoyant mother, decides to adopt a bullied misfit into his gang of outsiders. Left to their own devices, the boys explore aggression and violence but also learn about loyalty and love. As the group's behavior escalates towards life-threatening situations, Addi begins to experience a series of dreamlike visions. Can his newfound intuition guide him and his friends back to a safer path, or will they dive irrevocably into further violence?